Biotechnology in cartoons - Renneberg, Reinhard ; Berkling, Viola ; Chow, Ming Fai (2020)
The book introduces to the basics of biotechnology and lets young and old cartoon fans enjoy science in a relaxed and comprehensive way. Together with Professor Nanoroo, the story's likeable protagonist, the reader discovers on how biotechnology influences our daily life. The real science behind the funny cartoons is explained briefly in separate boxes. The Story: A shooting star falls to Earth in the Kingdom Macronesia. When King Richard VIII. examines the stardust under a super microscope, he discovers a small nanoscopic intelligent being in a micro-spacecraft ... Professor Nanoroo came down from planet Nano to Earth to understand human biotechnology. Curious, he communicates with ℓ́ℓEarthlingsℓ́ℓ, all asking hundreds of questions relating their life. Nanoroo encounters bread baking and beer brewing yeasts; disease makers and health- stabilizing bacteria; fungi producing drugs against bacteria. He experiences many adventures, rescues the king's brother from a heart attack, measures King Richardℓ́ℓs glucose level and the fitness of his racehorses, watches plants with their insect repellents and eats the famous and vitamin-rich ℓ́ℓGolden Riceℓ́ℓ. The real science behind the funny cartoons is explained briefly in boxes. While Nanoroo at his happy end departs from the Earth with the promise to come back, young and old cartoon fans have already enjoyed the basics of biotechnology in a relaxed and comprehensive way.